Correction: Sanzani et al. Design and Construction and Energy Consumption Study of a New Electrolyzed Water Cell Generator Prototype for Food Disinfection. Sci 2024, 6, 43 - Simona Marianna Sanzani; Pasquale Catalano; Gianluca Tanucci; Ferruccio Giametta; Antonio Ippolito; Biagio Bianchi (Sci)
In order to facilitate readers’ better understanding, some language descriptions and grammar as well as the layout of some chapters have been modified [...]